A Patient-Centered Environmental Scan of Inpatient Visitor Policies During the COVID-19 Pandemic. (October 2021) - Harrison, James D; Weiss, Rachel; Radhakrishnan, Nila S; Hanson, Catherine; Carnie, Martha B; Evans, Patricia; Banta, Jim; Symczak, Gina; Ziegler, Georgiann; Holmes, D'Anna; Michel-Leconte, Safia J; Rogers, Beverly; et al.
Researchers and patients conducted an environmental scan of policy documents and public-facing websites and abstracted data to describe COVID-19 adult inpatient visitor restrictions at 70 academic medical centers. We identified variations in how centers described and operationalized visitor policies. Then, we used the nominal group technique process to identify patient-centered information gaps in visitor policies and provide key recommendations for improvement. Recommendations were categorized into the following domains: 1) provision of comprehensive, consistent, and clear information; 2) accessible information for patients with limited English proficiency and health literacy; 3) COVID-19 related considerations; and 4) care team member methods of communication.